2023
DOI: 10.20944/preprints202301.0457.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Profile of Serological (IgM/IgG) and Virological Markers of COVID-19 in Some Private Universities in Cameroon During the Pandemic

Abstract: Background: COVID-19 remains a rapidly evolving and deadly pandemic worldwide. This necessitates the continuous assessment of existing diagnostic tools for robust, up-to-date and cost-effective pandemic response strategy. We sought to determine the infection rate (PCR-positivity) and degree of spread (IgM/IgG) of SARS-CoV-2 in three university settings in Cameroon Method: Study volunteers were recruited from November 2020 to July 2021 among COVID-19 non-vaccinated students in three Universities from two region… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…This table presents liver impairment according to hepatitis C antibodies carriage (HCVAb) [26]. While several studies in community settings in Cameroon have also found similar women predominance trend [27,28,29,30], contrary results were more or less reported in rural area of foreign countries including Congo [31], Egypt [32],…”
Section: Liver Impairment According To Hepatitis C Antibodies Carriag...mentioning
confidence: 96%
“…This table presents liver impairment according to hepatitis C antibodies carriage (HCVAb) [26]. While several studies in community settings in Cameroon have also found similar women predominance trend [27,28,29,30], contrary results were more or less reported in rural area of foreign countries including Congo [31], Egypt [32],…”
Section: Liver Impairment According To Hepatitis C Antibodies Carriag...mentioning
confidence: 96%